The HIV Screening Cascade: Current Emergency Department-Based Screening Strategies Leave Many Patients With HIV Undiagnosed. (1st May 2021) - Mohareb, Amir M.; Patel, Anuj V.; Laeyendecker, Oliver B.; Toerper, Matthew F.; Signer, Danielle; Clarke, William A.; Kelen, Gabor D.; Quinn, Thomas C.; Haukoos, Jason S.; Rothman, Richard E.; Hsieh, Yu-Hsiang
Abstract : Supplemental Digital Content is Available in the Text.